Associations of Hidradenitis Suppurativa with Atopic Dermatitis: A Review of Shared Pathogenesis and Approach to Treatment of Concomitant Disease - Rayad B. Shams; Hiral S. Patel; Christopher J. Sayed (Allergies, 2025)
Hidradenitis suppurativa (HS) and atopic dermatitis (AD) are both inflammatory dermatoses that can significantly impact patient quality of life, however, limited research exists regarding their association. The purpose of this comprehensive review is to compare the inflammatory pathogenesis of HS and AD, explore the associations between these diseases, and discuss standalone and concomitant disease treatment options. Although HS and AD are understood to be primarily driven by the Th1 and Th2 inflammation pathways, respectively, these conditions both utilize the Janus Kinase/Signal transducer and activator of transcription (JAK/STAT) pathway to promote inflammation. Newer research also suggests that IL-36 and IL-1 receptor-associated kinase 4 (IRAK4) may be two additional inflammatory signals shared between the HS and AD disease pathways. These shared mechanisms are reflected in patient presentations as HS and AD are often concomitantly present and demonstrate a bidirectional association in the current literature. Treatment options for concomitant disease are limited, but leverage the shared immune pathogenesis of both diseases. Dupilumab has been reported to improve both HS and AD symptoms in select patients. JAK inhibitors are currently FDA-approved for the treatment of AD, and early trials have suggested benefits from JAK inhibitors such as upadacitinib, povorcitinib, and topical ruxolitinib for HS. Possible future avenues for research on treating both HS and AD include IRAK-4 inhibitors such as zabedosertib and BAY1830839, and diet and gut microbiome modifications.